Effect of Fiscal Decentralization and Revenue Allocation on Local Government Performance: The Nigerian Experience (Journal of Governance and Development (JGD), 2014)
In federalism, ï¬ scal decentralization becomes an important pre-condition upon which the practice of good governance revolves, because it is anchored on efï¬ cient resource mobilization and utilization to ensure widespread participation and adequate representation. To facilitate good governance, the Nigerian state is politically structured into three governmental tiers: the federal, the state and the local government. However, evaluation of the performance of Nigerian local governments in terms of social service delivery depicts a massive failure. This paper therefore seeks to examine whether there is a nexus between local government failure and the nature of ï¬ scal decentralization and revenue allocation in Nigeria. The paper present key issues, trend and challenges in the operation of ï¬ scal decentralization in Nigeria. For instance, all decisions on revenue generation are controlled by the center and the vertical revenue allocation is structurally inclined toward the federal government, which negates the tenets of federalism and hence; grossly affects the capability of both the state and the local government to exercise ï¬ nancial autonomy. In conclusion, the paper offers some important suggestions which can galvanize the ï¬ scal capacity of the local government, thereby transforming them into viable machineries of social service delivery at the grassroots.